A gradient Al/Ni-Cr-Al layer formed by direct current pulse metal inert gas welding combined laser cladding on AZ91D magnesium alloy. (July 2019) - Pei, Xiaolong; Li, Zhiyong; Zhang, Yingqiao; Wei, Shouzheng; Yang, Liuqing; Wang, Yongji
Abstract: A gradient modified layer, containing an Al-Si interlayer and a Ni-Cr-Al top layer, was formed by direct current pulse metal inert gas welding combined laser cladding on AZ91D magnesium alloy. Firstly, the direct current pulse metal inert gas welding was used to prepare an interlayer with enough thickness on the surface of AZ91D magnesium alloy. After that, a pulsed YAG laser was applied to clad Ni-Cr-Al powders on the interlayer to form a top modified layer with higher micro-hardness and better corrosion resistance. The SEM, EDS and XRD results show that the interlayer is mainly composed of α-Al, Al + Al3 Mg2 and Mg2 Si while the top layer is mainly composed of α-Al, Al3 Ni, Al45 Cr7, Mg2 Si and Al + Al3 Mg2 . Furthermore, Y2 O3 was added to ameliorate the microstructure and properties of the gradient layer. The addition of Y2 O3 could refine the grain size, forming uniform microstructure in the top layer. The micro-hardness of the top layer is about five times higher than that of the AZ91D substrate and two times higher than that of the interlayer. The micro-hardness and corrosion resistance of the top layer were enhanced with the addition of Y2 O3 . Highlights: A thick gradient modified layer, containing an interlayer and a top layer, was formed by DC-PMIG welding combined laser cladding on AZ91D magnesium alloy. The microstructure and compositions of the gradient layer were studied by SEM, EDS and XRD. Y2 O3 was added to improve the micro-hardness and corrosion resistance of the top layer. The results showed that not only the top layer, but also the interlayer could protect the AZ91D substrate.